Tinjauan Literatur: Pengaruh Dukungan Sosial, Pengucilan Sosial, dan Transportasi terhadap Partisipasi Suami dalam Program Keluarga Berencana - Restiana Dhivana Julieta (Universitas Airlangga, 2023)
Background: The Family Planning Program is a national scale program to reduce birth rates and control population growth. The family planning program in Indonesia was initiated in the 1950s, but there were many obstacles in realizing the program so that the family planning program was only able to run in the 1970s. Purpose: The purpose of this study was to see the effect of social support, social exclusion, and transportation on husband's participation in family planning programs Method: the research was conducted by means of a literature review, namely searching for national and international journal articles based on keyword criteria, namely having a relationship with the topic of discussion, then obtaining 15 articles reviewed. Results: Several studies have shown that motivational factors are indeed important in increasing husbands' desire to participate. Apart from support, men's participation is also influenced by factors of knowledge, attitude, economy, culture and religion. Conclusion: Social support and transportation have a very big role to play in supporting husbands to be able to participate however, the existence of social exclusion or ostracism is also a factor in the low participation of husbands.